Rancang Bangun Alat Monitoring Ketinggian Air Sawah Berbasis SMS Gateway Di Sawah Andiang - Aslam Nasyiith; Jufrizel; Hilman Zarory; Putut Son Maria (APIC, 2023)
Indonesia is an agricultural country where part of the population works in agriculture. Currently, the measurement of the water level of rice fields in Andiang rice fields still uses manual methods by placing restrictions on rice field irrigation then farmers check their condition periodically directly to the field. From this problem, some prototype is needed to do some monitoring from the condition of rice field waters and send notifications to rice field owners. The purpose of this research is to make a prototype that makes it easier for farmers to monitor the condition of rice field waters so that they do not experience overflow or drought. The method used is research and development to improve existing products by testing their effectiveness. This prototype utilizes HC-SR04 (ultrasonic sensor) as a water level reader and SMS Gateway as a platform in sending and receiving SMS (Short Message Service) from mobile phones. The result of this research is that this prototype is able to monitor the water level of rice fields in Andiang Rice Fields.